Developing Mathematical Creativity in Early Grades: Impact Analysis of Geometric Problem Solving on Student Cognitive Levels - Afifah, Ani; Karim, Samuel (Universitas Nahdlatul Ulama Surabaya, 2025)
In today's digital era, critical and creative thinking skills are crucial for students to adapt to the demands of the 21st century. Creative and effective teaching, such as geometric problem solving, is considered an attractive strategy to enhance these skills. This study was conducted to evaluate the impact of geometric problem solving teaching on students' cognitive development at the elementary level, where previous research has focused more on the development of cognitive and psychomotor skills. The main objective of this study was to analyze the level of mathematical creativity of early grade students in solving geometric problems involving triangles and quadrilaterals. Using a qualitative descriptive approach, this study involved three students with different levels of mathematical ability. Data were collected through validated problem-solving tasks, in-depth interviews, and documentation, then analyzed based on indicators of fluency, flexibility, originality, and elaboration. The results showed significant differences in students' cognitive levels: students with high ability achieved Creative Thinking Level (CTL) 4, students with medium ability achieved CTL 2, and students with low ability achieved CTL 0. The integration of non-routine geometric problems from the early grades is crucial for mapping and stimulating students' creative potential. These findings provide practical implications for educators in designing inclusive learning interventions to accelerate the achievement of basic numeracy literacy and 21st-century skills in accordance with the global mandate of the SDGs.